Hardness properties of calcium and magnesium ions in drinking water - Yonca Pinar Ingin; Daniel Mahringer; Fatima El-Athman (Applied Food Research)
The drinking water parameter - water hardness - is defined as the sum of calcium and magnesium ion concentrations. In this study, their precipitation during boiling was investigated, using water of different hardnesses, calcium to magnesium ratios, natural tap and bottled waters. During boiling, pH value, conductivity, and calcium and magnesium concentrations were measured. Further, the morphology and composition of precipitates were analyzed. Boiling tests with durations of 30 min showed only a decrease of calcium concentration by precipitation. Longer boiling of water with a high proportion of magnesium showed decreasing magnesium concentrations once the calcium precipitation was completed. Calcium carbonate precipitated as calcite and aragonite crystals with aragonite needles occurring in the presence of high magnesium concentrations. Magnesium hydroxide formed during precipitation was identified as hydromagnesite crystals with different crystallization morphologies. Unexpectedly, for a water with low and equimolar concentrations of calcium and magnesium only magnesium precipitated at the relatively low pH 8.7. In summary, calcium ions in drinking water are evaluated as being of considerably higher relevance for the hardness properties than the magnesium ions. However, the precipitation of both minerals depends on their concentrations and ratio as well as on the pH value and the water matrix.